The Influence of Perceived Risk on Trust, E-WOM, and Purchase Intention in Shopee Users - Pratama, Rizky Yudha; Harsono, Soni (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2025)
This research aims to test and analyze the influence of risk perception on trust, trust in E-WOM and purchase intentions of Shopee users. This type of research is quantitative with a relational approach. The population of this research is Shopee users and the sample is Shopee users in Surabaya. The sampling technique uses purposive sampling with certain criteria and a sample size of 155 respondents. Data was collected through a questionnaire with five Likert scale measurements for all variables. This research uses Structural Equation Modeling - Partial Least Square (SEM-PLS). Validity and reliability tests have been carried out, the results are that all indicators are valid, and all variables are declared reliable. The research results confirm that perceptions of perceived risk have a negative and significant effect on trust, trust has a significant positive effect on E-WOM and purchase intentions of Shopee users. This research shows that Shopee users really consider risk when buying products on Shopee, apart from that trust is an important factor in E-WOM and also purchase intention.